Analisis Pengaruh Curah Hujan terhadap Produksi Padi dalam Mendukung Ketahanan Pangan di Indonesia: Pendekatan Regresi Data Panel - Anisa Sa'baniyah; Laila Najmi Rei; Edy Widodo (Universitas Galuh, 2026)
Food security in Indonesia plays a crucial role in maintaining national social and economic stability, given that most of the population still depends on rice as their staple food. The sustainability of rice production is a major factor in supporting food security, but the agricultural sector is highly vulnerable to climate change, particularly rainfall fluctuations and uncertainty. Changes in rainfall patterns have the potential to disrupt the rice growth process, change planting patterns, and reduce crop productivity. This study aims to evaluate the impact of rainfall on rice production in supporting food security in Indonesia. This analysis applies a panel data regression methodology that combines period and region coverage. The data used are rice production, harvest area, and population data available on the BPS website, while rainfall data are from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), with the unit of analysis being all provinces in Indonesia. The research variables include rainfall, harvested area, and population as independent variables and rice production as the dependent variable. The analysis method uses a panel data model approach, namely the Fixed Effect Model (FEM) and Random Effect Model (REM). The best model is selected through the Hausman test. The results of this study are expected to indicate that rainfall affects rice production, with variations in impact between regions and time periods. These findings are expected to form the basis for the formulation of agricultural policies and climate change adaptation strategies to maintain national food security.